The Influence of Service Quality and Product Features on Purchase Decisions (Case Study of the Avanza Car PT. Toyota Agung Soekarno-Hatta Pekanbaru) - Rasyid Ridho; Mashur Fadli (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the influence of service quality and product features on purchasing decisions. This research was conducted at a transportation company, namely PT. Toyota Agung Soekarno Hatta Pekanbaru. This research used 128 respondents who were consumers of PT. Toyota Agung Soekarno Hatta Pekanbaru. In this research, the sampling technique used was Accidental Sampling or anyone found by chance. Numerous tests were conducted for this study, including validity assessments, reliability assessments, tests for heteroscedasticity, multicollinearity, and normalcy, as well as hypothesis testing. Multiple linear regression is the analytical technique that is used. The study's findings demonstrate that product attributes and service quality have a favorable and substantial impact on consumers' choices to buy.